2021
DOI: 10.1021/acs.biochem.1c00306
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Protein Degradation to Understand Genome Architecture

Abstract: We review exciting recent advances in protein degradation, with a focus on chromatin structure. In our analysis of the literature, we highlight studies of kinetic control of protein stability for cohesin, condensin, ATP-dependent chromatin remodeling, and pioneer transcription factors. With new connections emerging between chromatin remodeling and genome structure, we anticipate exciting developments at the intersection of these topics to be revealed in the coming years. Moreover, we pay special attention to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 98 publications
(154 reference statements)
0
5
0
Order By: Relevance
“…The elusive relationship between RNA transcription and genome conformation has been a major focus in recent literature. 1 Of note, a study from Hsieh et al 5 uses integrated chromatin structural sequencing and imaging to uncover a large degree of independence between the major players of mammalian chromatin structure (cohesin, CTCF, WAPL) and RNA expression. Combining the nucleosome sensitivity of MNase and the in situ components of Hi-C (Micro-C), the authors find that rapid inducible depletion of cohesin complexes only affects a small fraction of the exome.…”
Section: Chromatin Remodeler Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…The elusive relationship between RNA transcription and genome conformation has been a major focus in recent literature. 1 Of note, a study from Hsieh et al 5 uses integrated chromatin structural sequencing and imaging to uncover a large degree of independence between the major players of mammalian chromatin structure (cohesin, CTCF, WAPL) and RNA expression. Combining the nucleosome sensitivity of MNase and the in situ components of Hi-C (Micro-C), the authors find that rapid inducible depletion of cohesin complexes only affects a small fraction of the exome.…”
Section: Chromatin Remodeler Functionmentioning
confidence: 99%
“…The elusive relationship between RNA transcription and genome conformation has been a major focus in recent literature . Of note, a study from Hsieh et al uses integrated chromatin structural sequencing and imaging to uncover a large degree of independence between the major players of mammalian chromatin structure (cohesin, CTCF, WAPL) and RNA expression.…”
Section: Emerging New Roles For Cohesin and Chromatin Remodeler Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence indicates that chromatin domains can be targeted by clinical [ 11 ] or pre-clinical [ 9 , 29 ] chemotherapeutic strategies. New insights into the regulatory roles of topoisomerases have revealed the potential of the clinical molecule etoposide to covalently disrupt chromatin domains [ 11 ].…”
Section: Main Textmentioning
confidence: 99%
“…The recent analysis aimed at elucidating the dynamics of SWI/SNF function by inducible protein degradation or pharmacological inhibition showed that the loss of SWI/SNF activity results in a rapid closure of active chromatin ( 20 , 21 ). To address the question of whether or not the maintenance of stable chromatin accessibility also requires a continuous function of pioneer TFs, we adopted the degradation TAG (dTAG) system for inducible degradation of EBF1, tagged with FK506-binding protein (FKBP) ( 22 24 ). Here, we report that EBF1 is required for continuous BRG1 recruitment and maintenance of open chromatin regions.…”
mentioning
confidence: 99%